Intermediality as a Genre Dominant of the Screenplay - Matiychak, Aliona; Nikoriak, Natalia (Scientific Collection «InterConf», 2022)
The article analyzes the screenplay "Check Your Watches" by Lina Kostenko and Arkadiy Dobrovolskiy in the context of intermedial studies. This text appears as an original intermedial genre construct, presenting a synthesis of two types of art (literature and cinema), but it also actively appeals to other arts: painting, sculpture, theater, music and, intertextually, to literature. Artistic codes permeate different levels of the text: the title complex, personosphere, composition, presenting the versatility, uniqueness and aesthetic level of the scriptwriters. The "decoding" of the screenplay artistic codes takes a leading position in the appropriate conceiving of the authors’ intentions and overall understanding of the screenplay ideological subtext, that testifies to its multi-layered, extremely powerful receptive potential.
Keywords: intermedial code, intertext, screenplay, genre, reception